PENGARUH PEMBERIAN INSENTIF DAN KOMPETENSI KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL NIKITA BUKITTINGGI - Permana, Reyhan Busra; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted at the Nikita Hotel, which is located at Jalan Sudirman No. 55 Bukittinggi, West Sumatra. This study aims to determine the effect of incentives and work competencies on employee performance. This research used quantitative descriptive analysis method with SPSS program. The population and sample of this study were all employees of the Nikita Hotel Bukittinggi in 2019, totaling 42 employees.Data analysis used validity test, reliability test, simple linear analysis, multiple linear analysis, and hypothesis testing using the coefficient of determination (R2 test), partial test (t test), simultaneous simulative test (F test). The results of this study indicate the results of the t-test hypothesis with the incentive giving variable obtained t-count (3,922)> t-table (2,021) and Sig. (0,000) <0.05 means that partial incentives have a significant effect on employee performance. Second, using the competency variable obtained t-count 4.134> t-table (2.021) and Sig. (0.000) <0.05 means that competency partially has a significant effect on employee performance. The F test results of providing incentives and competencies on employee performance obtained F-count (42.048)> f-table (3.24) and Sig. (0,000) <0.05 means that the provision of incentives and competencies together has a significant effect on employee performance.Keywords: Incentives, Competence, Employee Performance.